First you need to distribute the negative to 5,3x and -4 now you have this:
-3.5x+7-5.3x +4 rearrange and combine like terms (matching x's with x's etc.)
-3,5x -5.3x +7+4
-8.8x +11 your final answer there are no more like terms that you can combine.
15 days
Hope this helps
Mark brainliest please
Answer:
The answer to your question is:
Step-by-step explanation:
12.-
x² - 6x = 5
x² - 6x + (3)² = 5 + (3)²
x² - 6x + 9 = 5 + 9
(x - 3)² = 14
13.- x² - 6x = 12
x² - 6x + (3)² = 12 + (3)²
x² - 6x + 9 = 12 + 9
(x - 3)² = 21
x - 3 = ±√21
x1 = √21 + 3 x2 = -√21 + 3
x1 = 7.58 x2 = -1.58
14.- 2x² - 24x = - 20 Divide by 2
x² - 12 x = -10
x² - 12x + (6)² = - 10 + (6)²
x² - 12x + 36 = - 10 + 36
( x - 6) ² = 26
x - 6 = ±√26
x1 = √26 + 6 x2 = -√26 + 6
x1 = 11.1 x2 = 0.9
Answer: x= -1
Step-by-step explanation:
First you take 4 and times it to x and -1, so 4 times x will just be 4x while 4 times -1 will be -4. Then it will look like this (4x - 4), you will have to make the x by itself and to do that is dividing it by 4 on both sides, so 4x/4= x while -4/4= -1. The answer is x= -1
It means your solving for x